Zur Vitalitaet slavischer Idiome in Deutschland - Achterberg, Jörn (Slavistische Beitraege, 2005)
Germany has gradually become Europe's largest immigration country and is increasingly shaped by the image of a multicultural and multilingual society. However, the issue of multilingualism receives little attention, especially with regard to Slavic migration idioms. The aim of the present study is the empirical investigation of the current language behavior of Slavophone immigrants and the determination of the vitality of their native languages. On the basis of a nationwide survey of 500 immigrants detailed microsociological data on the use of Slavic languages ​​depending on persons, topics and situations will be collected and the influence of linguistic ecological factors such as attitudes, motivations, identity and social network of speakers on language use and language content will be investigated. In addition, on the basis of interdisciplinary approaches to the description of linguistic minorities, the vitality of slavins is analyzed comparatively, showing the current situation and the future development of Slavia in Germany in general and specific tendencies of ethnolects in particular.